Enhancing the performance of composite phase change materials using novel triply periodic minimal surface structures - Fok, Priscilla Jia Yuan (2024)
Organic phase change materials (PCMs) are widely used in thermal management applications owing to their high latent heats of fusion and low cost. Unfortunately, their poor thermal conductivities severely hamper the thermal transport process. Hence, PCMs are often hybridized with high thermal conductivity materials that promote phase change for time-sensitive applications and potentially increase the power density of thermal energy storage (TES) devices. Optimized thermally conductive networks with high-latent-heat PCM matrices are critical in the thermal management of high heat flux applications. With advancements in additive manufacturing, it has become easier to create complex topologies, such as triply periodic minimal surfaces (TPMS), that can further augment the performance of composite PCMs. TPMS surfaces have shown great promise in improving thermal transport performance but investigations into their thermal properties remain limited. In this study, the thermal performances of PCM infused TPMS structures of wall thicknesses varying from 0.4 mm to 0.8 mm were systematically investigated. The TPMS structures were designed using level-set equations, and each system of structures was fabricated by selective laser melting, a metal additive manufacturing technique. Numerical investigations were performed to understand the phase change dynamics of PCM in TPMS cells and experiments were performed to determine their thermal properties and phase change performance for thermal energy storage applications. Our simulations revealed that for structures with uniform wall thickness of 0.4 mm, the novel Neovius structure resulted in the highest effective thermal conductivity enhancement. For a given thickness, it is thus hypothesized that more complex TPMS topologies have higher surface areas and volumes which enhance their thermal conductivities. However, the complex shape of the Neovius structure could not be further uniformly thickened without self-intersecting geometries. Ultimately, a balance of both the surface area and thickness of the TPMS cell determines the thermal conductivity enhancement. Overall, the 0.6 mm thick IWP cells had the highest thermal conductivity of 13.84 W/m K, which was consistently verified in experiments. This is likely due to the fact that it has a larger surface area than the P structure but is also thicker than the 0.4 mm Neovius structure. To further demonstrate the potential application of our PCM-based TPMS design, low temperature thermal cycling tests were performed. Our results showed the IWP cell structure promoted a more uniform temperature distribution as compared to the P cell. Phase change in the 0.6 mm thick IWP cell structure was completed 1.4 times faster than the 0.8 mm thick P cell and 1.8 times faster than the 0.6 mm thick P cell. The purpose of this study is to provide useful guidelines for the selection of TPMS structures for various applications such as battery packs and spacecraft and to open doors for the co-optimization of materials and device geometry for enhanced energy and power density.